2014
DOI: 10.1016/j.quascirev.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Tephrochronology and the extended intimate (integration of ice-core, marine and terrestrial records) event stratigraphy 8–128 ka b2k

Abstract: The comparison of palaeoclimate records on their own independent timescales is central to the work of the INTIMATE (INTegrating Ice core, MArine and TErrestrial records) network. For the North Atlantic region, an event stratigraphy has been established from the highprecision Greenland ice-core records and the integrated GICC05 chronology. This stratotype provides a palaeoclimate signal to which the timing and nature of palaeoenvironmental change recorded in marine and terrestrial archives can be compared. To f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 124 publications
0
52
0
Order By: Relevance
“…Lowe, 2011 for an extensive review). In the Mediterranean region, the use of tephra layers as chronological and stratigraphic markers (Wulf et al, 2004Zanchetta et al, 2011Zanchetta et al, , 2012aBlockley et al, 2014;Albert et al, 2015;Giaccio et al, 2015) has largely improved our ability to synchronize archives and proxies, and to recognize leads and lags between different paleoclimate records (e.g. Regattieri et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Lowe, 2011 for an extensive review). In the Mediterranean region, the use of tephra layers as chronological and stratigraphic markers (Wulf et al, 2004Zanchetta et al, 2011Zanchetta et al, , 2012aBlockley et al, 2014;Albert et al, 2015;Giaccio et al, 2015) has largely improved our ability to synchronize archives and proxies, and to recognize leads and lags between different paleoclimate records (e.g. Regattieri et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…2). The "old-change test" compared three Blockley et al (2014). N e 283 values were sampled uniformly in the interval 10,000-2,000,000.…”
mentioning
confidence: 99%
“…See Table S1 for a complete list of all Late Pleistocene sites from which bone samples were retrieved. O levels over the last 130 thousand years (Blockley et al, 2014), which is the temperature proxy that our two palaeoclimate models are directly based upon. The PCRM (palaeoclimate records model) predicts population growth during warm periods, while in the PCRM -1 (the inverse of PCRM) populations increase in size during periods of cold climate.…”
mentioning
confidence: 99%
“…cold oscillations) culminating in the late-glacial Stadial (Younger Dryas) before the rapid warming at the beginning of the Holocene at 11.7 ka BP (Walker et al 2009). Recent work by the INTIMATE project utilising tephrachronology (Blockley et al, 2012) has allowed regional event stratigraphies to be identified which although broadly phase-locked to the Greeenland NGRIP record do show significant variations which were manifest by regional to local variations in vegetation cover (Walker et al 2012). The lack of well-developed soils and high rates of climate change promoted moderate to high ecological disturbance regimes with a high prevalence of, what we would recognise today as, early successional stages.…”
Section: A Recent Analysis Of the Distribution Of Lower Palaeolithic mentioning
confidence: 99%